Assessment of household energy efficiency in Ibadan, Nigeria (2012)
Household require significant amount of energy to meet various services like lighting, cooling, heating, cooking, refrigeration, electronic entertainment, e.t.c. There’s virtually any household activity that can be carried out without the use energy. The requirement for household energy in Nigeria has been growing over time. There are various energy sources available to households in the country. They include fuel, wood, charcoal, sawdust, gas, petrol, kerosene and electricity. It is fairly settled from literatures that electricity is the cheapest and cleanest energy source available. However, Nigeria, with a population of over 150 million people only has about 40% of its population having access to electricity with most of the people with access living in the urban centers (UNDP, 2011). Access to electricity in Nigeria is the dividing line between the urban areas and the rural areas. It can be said that Nigeria is suffering from “ Energy Poverty”. For a nation that seeks to attain the status of developed economy, the issue of energy poverty must be resolved fast.